Sinkhole Risk Assessment in the Metropolitan Area of Napoli, Italy. (2016) - Santolo, Anna Scotto di; Forte, Giovanni; De Falco, Melania; Santo, Antonio
Abstract: The city of Naples and its neighboring is an example of urban area affected by frequent anthropogenic sinkholes. They occur where the mining of tuff at shallow depth left a wide and complex network of cavities. The collapse is usually triggered by the soaking of the overlying pyroclastic soils forwarded by the presence of leakage from aged aqueducts and sewerages. This note reports the first results of a multidisciplinary research activity aimed at enhance the knowledge of the triggering factors of these phenomena in urban contexts. The study focused on an area characterized by the presence of cavities dug in tuff, starting from the research and collection of their location and that of past collapse events. In particular, the paper presents the results of sinkhole occurrence assessment at both local and metropolitan scale. In the first case, in order to define the most likely triggering mechanisms a case study among the recent sinkholes was investigated. A detailed field survey of the phenomena permitted to define the stratigraphical and geometrical setting of the pre-existing cavity and collect soil and rock samples for the geotechnical characterization. The attained results permitted to identify the most relevant parameters that influence the susceptibility assessment in a study area at metropolitan scale. This study represents contribute to the definition of a procedure to study anthropogenic sinkhole in intensely urbanized areas and it represents a valuable support for future planning strategies of risk mitigation.